IMPLEMENTASI PENGGABUNGAN PROGRAM TASMI’ DENGAN MUROJA’AH DALAM MENINGKATKAN KUALITAS HAFALAN SANTRI PONDOK PESANTREN MADRASATUL QUR’AN TEBUIRENG JOMBANG - Nida, Dewi Yukha; Said, Ali (EL-Islam, 2021)
Abstract: The author conducted a study on "Implementation of the Merging of Tasmi' and Muroja'ah Programs in Improving the Quality of Memorizing Santri of the Madrasatul Qur'an Islamic Boarding School Tebuireng Jombang" by using the research focus on How to implement the merging of the tasmi' program with muroja'ah in improving the quality of memorization of the students of Pondok Pesantren Madrasatul Qur'an Islamic Boarding School Tebuireng Jombang. This research is included in qualitative research. In this case, the researcher will collect data about the implementation of the tasmi 'combination program with muroja'ah for bil-ghoib graduate students in three ways, namely: observation, interviews, and documentation. The type of research used is phenomenology. The data analysis technique uses the theory of Miles and Huberman in the form of data reduction, data presentation, and data verification. And the technique of checking the validity of the data is using the triangulation technique. Based on this research, the results obtained: (1) The merging of the tasmi' program with muroja'ah at Madrasatul Qur'an is a program that is implemented at the Islamic boarding school as a requirement so that students can take part in the bil-ghoib graduation by depositing the memorization that has been deposited. to the listening ustadz then tasmi'kan (heard) to the listener assigned by the tahfidz unit, (2) The implementation of the merging of the tasmi' program with muroja'ah is very effective in improving the quality of student memorization because this method can make memorization stronger and inherent in students' memorization. Memory.